GC-MS Analysis of Amino Acids in Food Chain of Key Species Anchovy (Engraulis japonicus) of the Yellow Sea and East China Sea Food Web - Liu1, Hai-Zhen; Cai3, De-Ling; Luo1, Lin (Asian Journal of Chemistry, 2014)
Calanus sinicus and Engraulis japonicus were used in the experiment to understand the transfer process of amino acids in food chain. Through 76 days' experiment, a quantitative analysis of 14 kinds of amino acid content was carried in collected samples. The results showed that, Calanus sinicus played a connecting role in the food chain, it not only transferred plant protein into animal protein, greatly improved lysine content, but also increased total amino acid content of chlorella from 6.10 to 24.16 %. As the main economic fish in the food chain, Engraulis japonicus further increased amino acid content to 27.06 %. In terms of the relationship between Calanus sinicus's amino acid composition and Chlorella ( r = 0. 606, p < 0. 05 ), the correlation of 7 essential amino acids was relatively weak, while the correlation of 7 non-essential amino acids was obviously stronger. When anchovy's bait was changed from synthetic bait to Calanus sinicus, its amino acid content changed to some degree, before the change, it was related to synthetic bait, after the change, it was more closely related to Calanus sinicus. Amino acid content of anchovy feces was mainly decided by physiological processes of metabolism.